AKTIVITAS ANTIOKSIDAN DAN MUTU TEH HERBAL DAUN MANGGA BERDASARKAN LETAK DAUN PADA RANTING - Muhammad Zikmi Pulungan; Faizah Hamzah; Noviar Harun; Yossie Kharisma Dewi (Jurnal Teknologi Pertanian Andalas, 2022)
This study aims to obtain antioxidant activity and the best quality of mango leaves herbal tea based on the location of the leaves on branches. The research has been experimentally using a completely randomized design (CRD) with 4 treatments and 4 replications, so that 16 experimental units obtained. The treatments used were P1: Leaf shoots, P2: Young mango leaves (numbers 1-3 after the shoot), P3: Old mango leaves (numbers 4-6 after shoots) and P4: Oldest mango leaves (numbers 7-9 after shoots). Observations made on mango leaf herbal tea were water content, ash content, total phenol, antioxidant activity and sensory assessment. The data obtained from the observation analyzed statistically using analysis of variance (ANOVA) with IBM SPSS software version 23. The results showed that the best treatment for mango leaf herbal tea based on the location of the leaves on the selected branches was the P1 (leaf shoot) treatment because it had very strong antioxidant activity. The antioxidant activity of P1 treatment with IC50 value was 25,91ppm, total phenol was 25.90%, water content was 9.95%, and ash content was 2.42%, with a descriptive green-yellow color, slightly mango leaf-scented and slightly bitter taste.